Research on geophysical response analysis and prediction technology of geostress in the shale gas area of the southern Sichuan Basin - Wang, Chang; Yin, Cheng; Shi, Xuewen; Zhang, Dongjun; Liao, Maojie; Zhang, Ruhua (Frontiers in Energy Research, 2024)
The exploration and development potential of shale gas reservoirs in Sichuan Basin is enormous, however it also faces difficulties such as complex structures, strong heterogeneity and unclear geophysical response characteristics. Fine prediction of geostress is an important part of shale gas exploration and development, which directly affects the implementation effect of reservoir evaluation, well trajectory design and fracture reconstruction. The existing geostress prediction techniques lack high precision seismic data constraints, making it difficult to accurately reflect the planar distribution characteristics of the geostress in block with rapid changes in complex tectonic zones. At the same time, the geophysical response characteristics of geostress in Sichuan Basin are unknown, the geostress seismic prediction technology lacks theoretical basis. This paper combines numerical simulation and physical experiments, and defines the characteristics of geophysical response of shale gas reservoir in Sichuan Basin changing with stress field, and technical countermeasures for geostress seismic prediction are established to provide technical means for accurate prediction of geostress field in shale gas block. Based on the geostress sensitive parameters obtained from prestack seismic inversion, the geostress field prediction of a Shale gas work area in Sichuan Basin is realized.